If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2m + 5) = 3m + -5 Reorder the terms: 2(5 + 2m) = 3m + -5 (5 * 2 + 2m * 2) = 3m + -5 (10 + 4m) = 3m + -5 Reorder the terms: 10 + 4m = -5 + 3m Solving 10 + 4m = -5 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 10 + 4m + -3m = -5 + 3m + -3m Combine like terms: 4m + -3m = 1m 10 + 1m = -5 + 3m + -3m Combine like terms: 3m + -3m = 0 10 + 1m = -5 + 0 10 + 1m = -5 Add '-10' to each side of the equation. 10 + -10 + 1m = -5 + -10 Combine like terms: 10 + -10 = 0 0 + 1m = -5 + -10 1m = -5 + -10 Combine like terms: -5 + -10 = -15 1m = -15 Divide each side by '1'. m = -15 Simplifying m = -15
| -6(5p+6)+7(p+5)= | | -(v+4)+3= | | -5(3-x)+x= | | 15-3x=-6 | | 100t=10+70t | | 9x+4=8x-6 | | 5(-2-2x)-3= | | 6x-(4-7x)= | | 3(-7-3x)+x= | | -2n-3(5n-1)= | | 8-2(k-6)= | | c=b-bx | | 106+4n=58 | | -2(1-2a)-2= | | 4b-2b= | | -10x+2-8x= | | 6x-(4-7x)=3x-8(2+x) | | 5m-10m= | | 7n-6+n+1= | | r+3+9r-9= | | 5+3n+3n= | | 5x-2x= | | -6x(2-8x)-4x(x-6)= | | 4(3m+2)=2(6m+8) | | -5x(-7x+7)+4(x+4)= | | -2(2t-4)=-4(-1t+2) | | 5-8x=62-29x | | -3(x+13)=3 | | 3x+9=-9x | | -18-2x=10-9x | | 17-20q=(-13-5q)4 | | 82-2x=8x+22 |